Describing the Global Molecular Dynamics of Neurotransmitter Cycles: A Quantum Field Based Approach - Paul Levi (Newest Updates in Physical Science Research Vol. 12, 2021)
Descriptions of neurotransmitter cycles in chemical synapses are generally accomplished in the field of macroscopic molecular biology. This paper proposes a new theoretical approach to model these cycles with methods of the non-relativistic quantum field theory (QFT) which is applicable on small neurotransmitters of nano size like amino acids or amines. The whole cycle is subdivided into the standard five phases: uptake, axonal transport, release and reception. Our ansatz is concentrated to quantum effects, which are relevant in molecular processes. Examples are quantization of momentums and energies of all small transmitters, definition of the density-based quantum information, quantization of molecular currents, because densities of them generate quantized particles. Our model of the neurotransmitter cycle of chemical synapses was created by the emphasis of possible essential quantum effects; therefore, we neglect many additional molecular aspects that do not lead us to quantum impacts. We elucidate the ramification of our quantum-based approach by the definition of particular Hamiltonians for each of the five phases of the neurotransmitter cycles and by the calculation of the corresponding molecular dynamics. The transformation from the particle representation to usual wave functions yields the probability to find at the same time neurotransmitters of different energy states at different positions. Our results have far-reaching implications and may initiate animated discussions. The validation or the disconfirmation of our hypothesis is still open.